A "full spectrum-domain-time" coalbed gas utilization model and its application in mining area. Issue 4 (July 2021) - Linghu, Jianshe; Chen, Jinhua; Zhou, Jianbin; Jiang, Wangang
Coalbed gas (CBG) has been widely used as an important energy source. However, its utilization and allocation system is imperfect in mining areas. During the utilization process, a large amount of CBG is discharged into the air, causing environmental pollution. In this study, we proposed a "full spectrum-domain-time" CBG utilization model. In this model, by combining high methane concentration gas power generation, low methane concentration gas purification, and ultra-low methane concentration gas thermal storage and oxidation utilization, we were able to utilize CBG with full-spectrum of methane concentrations. In addition, by establishing CBG transportation and storage system in mining area, we were able to realize CBG supply in the entire network domain. Furthermore, based on the time series prediction algorithm, the CBG demand of different mining areas is predicted and regulatorily met by real time allocation. Through these three steps, an efficient "full spectrum-domain-time" CBG utilization system was formed and practically applied in Yangquan mining area. The application results showed that under the comprehensive control of "full spectrum-domain-time" CBG utilization model, CBG with methane concentration ≥0.2% could be used in the mining area and its utilization rate increased year by year, reaching the highest of 77.15%. Overall, our study provided a reference for the efficient CBG utilization in the mining area.